ИССЛЕДОВАНИЕ МАГНИТНОГО ПОЛЯ ТРЕХМЕРНЫХ ФЕРРОМАГНИТНЫХ ОБЪЕКТОВ - Резинкина, М.М.; Лобжанидзе, Л.Э. (Інститут електродинаміки НАН України, Київ, 2010)
Methodology of numerical calculations of magnetic field and magnetic moment of ferromagnetic objects with complicated space form has been described with the help of the method of final volume and absorbing boundary conditions. Calculations of magnetic field and magnetic moment in the row of ferromagnetic objects have been performed with developed methodology. Dependence of magnetic moments of ferromagnetic constructions on their geometric shape has been analysed. References 21, figures 5.